2009
DOI: 10.1002/bit.22212
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of immobilized polyplexes and lipoplexes for substrate‐mediated gene delivery

Abstract: Non-viral gene delivery by immobilization of complexes to cell-adhesive biomaterials, a process termed substrate-mediated delivery, has many in vitro research applications such as transfected cell arrays or models of tissue growth. In this report, we quantitatively investigate the efficiency of gene delivery by surface immobilization, and compare this efficiency to the more typical bolus delivery. The ability to immobilize vectors while allowing cellular internalization is impacted by the biomaterial and vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…This discussion provides some additional insight. First, because although the total amount of pDNA (active and inactive forms) present in a transfected cell is very high (Bengali et al 2009; Hama et al 2007; Hama et al 2006), the dissociation of active plasmid from the complex is a very rare event. Second, our cotransfection model, although it does not account for the existence of lipoplexes, is adequate provided plasmids are mixed together before adding the lipid reagent.…”
Section: Resultsmentioning
confidence: 99%
“…This discussion provides some additional insight. First, because although the total amount of pDNA (active and inactive forms) present in a transfected cell is very high (Bengali et al 2009; Hama et al 2007; Hama et al 2006), the dissociation of active plasmid from the complex is a very rare event. Second, our cotransfection model, although it does not account for the existence of lipoplexes, is adequate provided plasmids are mixed together before adding the lipid reagent.…”
Section: Resultsmentioning
confidence: 99%
“…Binding and release of lipoplexes to hydrogel surfaces was investigated to determine the kinetics of association and dissociation of the vectors to the affinity peptide without the complication due to physical entrapment [24]. Hydrogels containing 5 mM RDG, KDKG, K4, or K8 peptide were formed as described above in the absence of cells and DNA.…”
Section: Methodsmentioning
confidence: 99%
“…We, however, explored a different application of the growth factorbound affinity membrane as a substrate for cellular adhesion and proliferation. In addition, we used the negatively charged cellulose membrane to adsorb the cationic polymer-DNA polyplexes, which carry the growth factor-encoding gene, for substrate-mediated transfection (Lim et al 2006;Bengali et al 2009). We showed that the affinity cellulose matrices were capable of mediating both the peptide and transgene delivery of the growth factor.…”
Section: Introductionmentioning
confidence: 99%